Digital footprint as a new factor in forming students' social identity and character in the digital era - Alda Mafrikha Fauziah; Nur Khasanah (Sekolah Tinggi Agama Islam (STAI) AL-IKHLAS DAIRI SIDIKALANG, 2026)
Digital technology has transformed the way students develop their social identity and character. Digital footprints, which record every online activity, now function as a new factor that shapes self-perception, social relations, and moral behavior among students. This study aims to analyze the role of digital footprints in the formation of students' social identity and character in the digital era. Using a library research method, various scholarly articles, books, accredited national journals, and recent research were reviewed to construct a conceptual understanding of how digital practices influence identity development in educational settings. The findings reveal that digital footprints significantly affect the way students represent themselves online, interact with peers, and internalize social norms. Low digital literacy leads to identity distortion, negative self-presentation, cyberbullying, and impulsive digital behavior. Therefore, digital literacy education becomes essential in supporting the development of positive digital identity and character among students. The study concludes that schools must integrate digital literacy into character education programs to help students build responsible and ethical digital behavior